A CASE OF PAEDIATRICS OSTEOMYELITIS : REVISITED - Nik Abdul Adel, Nik Alyani; Abdul Razak, Ardilla Hanim; Awang, Shukrimi (2021)
A CASE OF PAEDIATRICS OSTEOMYELITIS : REVISITED NAA N.Alyani1, S. Fudhlana1, AR Ardilla Hanim1, A M.Shukrimi1 1 Department of Orthopaedic, Traumatology and Rehabilitation, Kulliyyah of Medcine, International Islamic University Malaysia, Kuantan, Pahang, Malaysia